Bouvard et Pécuchet et le désir amoureux - Anne Herschberg Pierrot (Flaubert: Revue Critique et Génétique)
This article presents a textual genetics study of Bouvard et Pécuchet’s 7th chapter, about love, which appears to be a surprising encyclopedic stage of the novel. Flaubert has fun writing these adventures in a not so tender country. This genetics study focuses on the writing of several key moments of the chapter (in the beginning and the duo scenes, such as the one between Mme Castillon and Gorgu). It reveals the erasure of erotic details, as well as politics and history, which end up condensed in the final text. It also shows this chapter’s concerted role in the construction of the novel and the characters’ development. Apparently minor, this chapter is emblematic of a poetics founded on the ellipsis, mingling play and seriousness.